(untitled) (Research, Society and Development, 2022)
Introduction: Systemic Arterial Hypertension is considered a chronic disease that affects an average of 15 to 20% of the adult population in the productive phase and more than 50% of the elderly. This pathology has several risk factors that can be classified as modifiable and non-modifiable. Social habits, stress, use of hormonal contraceptives, smoking, physical inactivity, eating habits, obesity and use of alcoholic beverages are part of the modifiable factors. Among the non-modifiable risks are: age, sex, heredity and race. General Objective: To analyze the hypertensive profile of patients treated at the Clínica Escola de Fisioterapia da Universidade de Gurupi, in the cardiorespiratory area, in the city of Gurupi, in the south of the state of Tocantins. Materials and Methods: Records of patients treated in the cardiorespiratory area were analyzed, from 2017 to 2022/1, being ≥18 years old. A statistical approach was used to analyze the collected data, with the help of the Microsoft Excel version 2016 program. The statistical analyzes of this research were performed considering the Student t test, with (p<0.05) for all variables. Results: The hypertensive profile that prevailed in patients treated at the Clínica Escola de Fisioterapia da Universidade de Gurupi, in the cardiorespiratory area, was the prehypertensive profile.